Pengaruh Fee Audit, Rotasi Audit, Audit Capacity Stress dan Ukuran Perusahaan Terhadap Earning Manipulation dengan Moderasi Kualitas Audit - F Agung Himawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2022)
The survey was conducted on 40 manufacturing companies listed on the Indonesian Stock Exchange during the observation period from 2016 to 2020. The sampling method used in this study was targeted sampling. The hypothesis of this study was tested using multiple regression analysis to measure the effect of the relationship between dependent and independent variables. The purpose of this study was to examine the variables Audit Fee (FA), Audit Rotation (RA), Audit Ability Stress (ACS), and revenue operation size representative of the Beneish M-score, with audit quality as a moderator variable, as experienced by manufacturing firms. to analyze it objectively. Listed on the stock exchange. effect. A sample of 40 and 200 Indonesian securities for the period 2016-2012. The results of this study show that the Beneish M-Score is highly influenced by exam fees, exam rotation, exam capacity load, and size. The FA variable has a 10% significant negative impact on profit manipulation (Beneish M-score). That is, the higher the audit fee accepted by management, the less evidence of manipulation of the financial statements. The RA variable has a very positive effect on profit manipulation. In other words, the more often audit rotations occur, the higher the likelihood of balance sheet manipulation. ACS variables have a significant negative impact on yield manipulation (beneish M-score) at = 10%. That is, the more audit clients, or the higher the ACS, the higher the monitoring that does not lead to manipulation of the financial statements. Finally, the size variable has a large positive impact on profit manipulation. H. The larger the company size, the more evidence of balance sheet manipulation. The results of the Model 2 study indicate that the presence of trial quality as a moderator variable can influence the relationship between FA, RA, ACS and size (Benish M score) in the profit manipulation. If the presence of audit quality (QA) weakens the impact of almost all variables on earnings manipulation (Benish m Score), this suggests that the presence of a reputable audit quality KAP enhances corporate scrutiny and reduces earnings manipulation and investor interest. It means avoiding useful information. and interested persons. Account holders and these factors are considered by investors and stakeholders to provide more relevant information.